2009
DOI: 10.2169/internalmedicine.48.1754
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related Bacteremia Caused by Agrobacterium radiobacter in a Hemodialysis Patient

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…R. radiobacter includes the former synonymic species Agrobacterium radiobacter and Agrobacterium tumefaciens, which could be differentiated only by the presence of tumorigenic (Ti) plasmids. R. radiobacter has been occasionally associated with opportunistic infections in humans, including bacteremia (especially catheter-related bacteremia) (2,4,9,11,15,16,21,22), pneumonia (17), urinary tract infections (1), peritonitis (12,26), and endocarditis (25). Most of these infections occurred in hospital settings (14), in patients with immunosuppression (e.g., hematologic malignancies, solid-organ cancers, HIV infection, or organ transplantation) (6,8,13,17), and/or in patients bearing a foreign material (e.g., central catheter) (4,11,14,15,21).…”
mentioning
confidence: 99%
“…R. radiobacter includes the former synonymic species Agrobacterium radiobacter and Agrobacterium tumefaciens, which could be differentiated only by the presence of tumorigenic (Ti) plasmids. R. radiobacter has been occasionally associated with opportunistic infections in humans, including bacteremia (especially catheter-related bacteremia) (2,4,9,11,15,16,21,22), pneumonia (17), urinary tract infections (1), peritonitis (12,26), and endocarditis (25). Most of these infections occurred in hospital settings (14), in patients with immunosuppression (e.g., hematologic malignancies, solid-organ cancers, HIV infection, or organ transplantation) (6,8,13,17), and/or in patients bearing a foreign material (e.g., central catheter) (4,11,14,15,21).…”
mentioning
confidence: 99%
“…7,8 Hastalar bakteriyemi, peritoneal diyaliz kaynaklı peritonit, üriner sistem enfeksiyonu ve nadir olarak da selülit, endoftalmit ya da pnömoni ile prezante olabilmektedir. Türki-ye'de ise ilk vaka olan ve 2008 yılında Taşbakan ve ark.…”
Section: Discussionunclassified
“…Several case studies reported infection of immunocompromised or other sensitive individuals by Agrobacterium radiobacter, most often causing blood(stream) infection or peritonitis (e.g. Hanada et al, 2009;Kato et al, 2009;Lai et al, 2004;Tsai, 2013), which were in some cases catheter-related. However, host sensitivity is a common risk-defining parameter in all reports retrieved, and Agrobacterium radiobacter strain K84 has been positively evaluated in the risk assessment and included in Regulation (EU) 540/2011.…”
Section: Pathogenicity Traits Of Selected Microorganisms Within the Smentioning
confidence: 99%